2013
DOI: 10.4329/wjr.v5.i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for deep brain stimulation: The zona incerta at 7 Tesla

Abstract: AIM:To evaluate different promising magnetic resonance imaging (MRI) methods at 7.0 Tesla (T) for the pre-stereotactic visualization of the zona incerta (ZI). METHODS:Two neuroradiologists qualitatively and quantitatively examined T2-turbo spin-echo (T2-TSE), T1-weighted gradient-echo, as well as FLASH2D-T2Star and susceptibility-weighted imaging (SWI) for the visualization of the ZI at 7.0 T MRI. Delineation and image quality for the ZI were independently examined using a 6-scale grading system. Inter-rater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 63 publications
1
21
1
Order By: Relevance
“…In addition, inconsistencies in the efficacy and adverse effects of ZI stimulation exist and likely reflect the inability to directly target the ZI resulting in variability of contact placement [20-23, 31, 32]. Methods for visualization of the rZI allowing direct stereotactic targeting have recently been reported [33, 34]. In addition, intraoperative microelectrode recordings may aide in direct targeting of the ZI as this region reveals a low amplitude background and a sparse cell density, as well as a lack of proprioceptive responses, which help to distinguish it from surrounding areas [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inconsistencies in the efficacy and adverse effects of ZI stimulation exist and likely reflect the inability to directly target the ZI resulting in variability of contact placement [20-23, 31, 32]. Methods for visualization of the rZI allowing direct stereotactic targeting have recently been reported [33, 34]. In addition, intraoperative microelectrode recordings may aide in direct targeting of the ZI as this region reveals a low amplitude background and a sparse cell density, as well as a lack of proprioceptive responses, which help to distinguish it from surrounding areas [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many explorations of the deep brain at ultra-high field (7-Tesla; 7 T) exploited T2w tissue properties enabling visualization of many deep brain nuclei with improved resolution and signal-to-noise ratio (SNR) including the RN, substantia nigra, and STN (Keuken et al, 2013;Plantinga et al, 2018;Schäfer et al, 2012), known to be rich in iron (Haacke et al, 2005;Luigi, Youdim, Riederer, Connor, & Crichton, 2004). Paralleling these successes, previous attempts at direct visualization of the ZI have focused on the use of T2w contrast, with purported identification of the rZI, but not the cZI (Kerl et al, 2013). In this study, we report that, by employing high-resolution longitudinal (T1) mapping at 7 T, robust visualization of the ZI and surrounding WM structures is possible in vivo along the entire rostrocaudal axis, allowing comprehensive anatomical characterization of this previously obscure deep brain region.…”
Section: Introductionmentioning
confidence: 99%
“…The ZI has proven to be elusive to visualization using T2w contrast. In one study at 7T, using a T2w 423 sequence, the rostral but not the cZI was reported as visible (Kerl et al, 2013), which we demonstrate is 424 actually the fasciculus lenticularis ( Figure 2). As a result, protocols for stereotactic targeting of the cZI have 425 relied on the relative visibility of the surrounding RN and STN, from which the location of the stereotactic 426 target within the PSA could be indirectly inferred.…”
mentioning
confidence: 56%
“…Many explorations of the deep brain at 7T have exploited T2w tissue 94 properties enabling visualization of many deep brain nuclei with improved resolution and signal-to-noise 95 ratio (SNR) including the RN, substantia nigra, and STN (Keuken et al, 2013;Plantinga et al, 2018;Schäfer 96 et al, 2012), known to be rich in iron (Haacke et al, 2005;Luigi Zecca et al, 2004). Paralleling these 97 successes, previous attempts at direct visualization of the ZI have focused on the use of T2w contrast, with 98 purported identification of the rZI, but not the cZI (Kerl et al, 2013). In this study, we report that, by 99 employing high-resolution longitudinal (T1) mapping at 7T, robust visualization of the ZI and surrounding 100 WM structures is possible in vivo along the entire rostrocaudal axis, allowing comprehensive anatomical 101 characterization of this previously obscure deep brain region.…”
mentioning
confidence: 99%